Advanced ferroelectric oxide films and heterostructures for unconventional applications - Sisi Huang; Cheng Ma; Kuijuan Jin (Advances in Physics: X)
Ferroelectrics, known for their reversible spontaneous electric polarization, have garnered significant interest in both fundamental physics and applications, such as non-volatile memories and sensors. To address the scattered nature of contemporary ferroelectric research, we write this review which extensively outlines the developments and recent progress on the most studied ferroelectrics, including lead-based and lead-free ferroelectrics, low-dimensional HfO2-based ones, high-entropy relaxor ones, and multiferroics. The tuning methods for these ferroelectrics, including strain, doping, and constructing interfaces, are also systematically discussed. In addition, we also summarize the applications of ferroelectrics, including ferroelectric diodes and ferroelectric tunnel junctions, synaptic devices, domain-wall-based devices, and photoelectric devices, highlighting their significant potential for advanced electronic and optoelectronic devices. This review gives a comprehensive summary of ferroelectrics and offers insights into future research.